PENGARUH PENERAPAN SUPPLY CHAIN MANAGEMENT DAN KAIZEN TERHADAP PROSES PRODUKSI DI PT. DAIKI AXIS INDONESIA - Andre Auritz; Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This research aims to know the effect of supply chain management and kaizen on company’s production. The Research method used is multiple linear regression analysis and simple linear regression analysis. The research result showed that supply chain management and kaizen togethers react positive and significant effect on production. The result is that partially supply chain management and kaizen each react positively and play significant role to production.